Telehealth ICT Infrastructures in the Nordic Countries:An Overview of the Current National Initiatives and Recommendations for the Future - Jørgensen, Daniel Bjerring; Hallenborg, Kasper (2015 17th International Conference on E-health Networking, Application & Services (HealthCom), 2015)
This paper presents an overview and recommendations of ICT infrastructures and reference architectures for telehealth in the Nordic countries (Denmark, Finland, Iceland, Norway, and Sweden). This study shows that so far only Denmark has designed a complete reference architecture, and by the end of 2015 Norway expects to complete their reference architecture. The foundation for both reference architectures is the framework by Continua Health Alliance. Of the remaining countries Sweden seems to be closing in on adopting Continua. So far, however, Sweden, Finland and Iceland has focused more on eHealth in general and not designed reference architectures or done implementations for telehealth specifically. This paper recommends that all the Nordic countries join Continua and collaborate to gain more influence of the organization’s decision making.